Fedora [videorecording (DVD)] - Wilder, Billy, 1906-2002; Holden, William, 1918-1981; Keller, Marthe; Ferrer, José, 1912-1992; Tryon, Thomas (Olive Films, 2014)
A film producer travels to the Greek isles to coax a Garbo-like screen idol out of seclusion. But the deeper he infiltrates the remote villa, evading an overprotective countess and a mysterious plastic surgeon, the closer he comes to discovering the terrible secret behind the actress's timeless beauty.